Changes in the Lifestyle of Overseas Students Due to the Era of Globalization in Makassar City - Muh. Watif M; Nurhikma Wulandari Agus; Nia Suaib; Risdawati; Nadia S. Alam (Journal AGENCY, 2024)
The capital of South Sulawesi province is Makassar City. The population consists of villagers and indigenous people. Many young people from various regions want to continue their higher education at state campuses in the city. Apart from that, there is the globalization process itself which began with advances in information and communication technology. This research tries to find out how student lifestyles have changed due to globalization in the city of Makassar. This research is descriptive qualitative in nature. The techniques used to collect data are documentation, interviews and observation. The qualitative analysis method is the analysis technique used. Meanwhile, the final results of this research show that globalization has a significant influence on changes in the culture and lifestyle of students in the city of Makassar. Considering that modernization and globalization are very important for progress, it is important to respond to this phenomenon in a wise way. Also, researchers know that there have been many lifestyle changes among overseas students in the city of Makassar. This change is influenced by internal and external factors. Several changes in student lifestyles, namely hedonism, consumption patterns, wearing branded clothing, changes in social habits, and habits of hanging out and behaving. Apart from that, there are also students who choose to live a simple life, even though they come from well-established families. This is done because they want to prioritize important things in their lives.